2016
DOI: 10.1523/eneuro.0158-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mechanisms of Recovery after Chronic Stroke: Modeling with the Virtual Brain

Abstract: We have seen important strides in our understanding of mechanisms underlying stroke recovery, yet effective translational links between basic and applied sciences, as well as from big data to individualized therapies, are needed to truly develop a cure for stroke. We present such an approach using The Virtual Brain (TVB), a neuroinformatics platform that uses empirical neuroimaging data to create dynamic models of an individual’s human brain; specifically, we simulate fMRI signals by modeling parameters associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 64 publications
(67 reference statements)
7
64
2
Order By: Relevance
“…In our previous work using TVB modeling in stroke patients [44], we found consistent parameter changes associated with poor long-term motor recovery. These included local hyper-excitability, lower conduction velocities in cortico-cortical connectivity, and an imbalance between local and global dynamics.…”
Section: The Virtual Brain-derived Models Are Sensitive To Disruptionsupporting
confidence: 70%
See 3 more Smart Citations
“…In our previous work using TVB modeling in stroke patients [44], we found consistent parameter changes associated with poor long-term motor recovery. These included local hyper-excitability, lower conduction velocities in cortico-cortical connectivity, and an imbalance between local and global dynamics.…”
Section: The Virtual Brain-derived Models Are Sensitive To Disruptionsupporting
confidence: 70%
“…In other words, the change in these parameters produced normalization of the balance between global and local dynamics and excessive excitation. Notably, these two parameters were those that correlated with long-term motor recovery in our previous work [44]. …”
Section: The Virtual Brain-derived Models Are Sensitive To Disruptionmentioning
confidence: 59%
See 2 more Smart Citations
“…A previous computational modeling study also reported alterations in inhibitory over excitatory coupling in chronic stroke patients (Falcon et al, 2016). It is difficult, however, to compare these results to those of our study, as Falcon and colleagues did not correct for region size or differentiate between affected and unaffected cortical areas.…”
Section: Discussionmentioning
confidence: 71%